GRASSROOTS GOVERNANCE AND RESILIENCE: THE ROLE OF BARANGAY DISASTER COMMUNICATION AMID POLITICAL UNCERTAINTY - Benigno, Karl Lenin Calaramo; Pilar, Elsie; Sabado-Lao, Yolanda (JWP (Jurnal Wacana Politik), 2026)
This study examines the role of barangay-level communication in disaster preparedness and response amid political uncertainty, focusing on Ilocos Norte, Philippines. Specifically, it investigates how comprehension of disaster warnings and COVID-19-related terms affects citizens’ compliance, and how demographic and barangay-related factors moderate this relationship. A mixed-methods approach was employed, involving surveys of 44 respondents (household heads, barangay officials, and Sangguniang Kabataan officers) and key informant interviews to document communication practices, sources of information, and community trust. Statistical analysis revealed a strong positive correlation (r = 0.843, p < 0.001) between comprehension and compliance, highlighting the critical role of understanding in disaster response. Findings also show that traditional communication channels, such as barangay announcements and personal networks, remain central, while political uncertainty can indirectly undermine trust and affect message adherence. Youth participation via SK initiatives contributes to information dissemination but requires enhanced resources and training. This study contributes novel insights by integrating statistical evidence, qualitative analysis, and political context to explain the dynamics of grassroots disaster communication. Policy recommendations include capacity-building, hybrid communication strategies, participatory governance, youth engagement, and integration of political risk into preparedness planning, aimed at enhancing resilience and adaptive capacity in local communities.